1999
DOI: 10.1091/mbc.10.8.2787
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Fourth Adaptor-related Protein Complex

Abstract: Adaptor protein complexes (APs) function as vesicle coat components in different membrane traffic pathways; however, there are a number of pathways for which there is still no candidate coat. To find novel coat components related to AP complexes, we have searched the expressed sequence tag database and have identified, cloned, and sequenced a new member of each of the four AP subunit families. We have shown by a combination of coimmunoprecipitation and yeast two-hybrid analysis that these four proteins (⑀, ␤4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
277
1
14

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(297 citation statements)
references
References 49 publications
5
277
1
14
Order By: Relevance
“…Although the most intensively studied aspect of BFA action is the ARFdependent recruitment of COP-I to Golgi membranes, it is also known that BFA induces alterations in the localization of markers of the TGN, specifically M6PR, resulting in increased staining at the plasma membrane. The recruitment of other coat complexes, specifically AP-1 (Stamnes and Rothman, 1993;Traub et al, 1993), AP-3 (Simpson et al, 1997;Faundez et al, 1998;Ooi et al, 1998), andAP-4 (Dell'Angelica et al, 1999;Hirst et al, 1999), has also been shown to be BFA sensitive and, thus, predicted to require active ARF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the most intensively studied aspect of BFA action is the ARFdependent recruitment of COP-I to Golgi membranes, it is also known that BFA induces alterations in the localization of markers of the TGN, specifically M6PR, resulting in increased staining at the plasma membrane. The recruitment of other coat complexes, specifically AP-1 (Stamnes and Rothman, 1993;Traub et al, 1993), AP-3 (Simpson et al, 1997;Faundez et al, 1998;Ooi et al, 1998), andAP-4 (Dell'Angelica et al, 1999;Hirst et al, 1999), has also been shown to be BFA sensitive and, thus, predicted to require active ARF.…”
Section: Discussionmentioning
confidence: 99%
“…Results from several laboratories have pointed to a central role for ARFs in regulating some aspect of membrane traffic, particularly to and from the Golgi, and more recently from the trans-Golgi network (TGN) (Stamnes and Rothman, 1993;Traub et al, 1993;Ooi et al, 1998;Hirst et al, 1999). ARFs were originally found to localize to the Golgi (Stearns et al, 1990b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best-studied function of Arfs is in the formation of COPI-coated vesicles from the Golgi (reviewed in Wieland and Harter, 1999). Arfs have also been implicated in the formation of a number of different vesicle coats and in many different steps in secretion (Balch et al, 1992;Boman et al, 1992;Lenhard et al, 1992;Stamnes and Rothman, 1993;Traub et al, 1993;Letourneur et al, 1994;West et al, 1997;Ooi et al, 1998;Hirst et al, 1999). Indeed, mutations of ARF1 in yeast result in pleiotropic defects in the processing of secreted proteins, as well as aberrant morphology of intracellular organelles (Stearns et al, 1990b;Gaynor et al, 1998;Yahara et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, AP-3 does not associate with clathrin (19 -22). Yet another recently described adaptor protein, AP-4, has no known function (24,25).…”
mentioning
confidence: 99%